Kidney transplantation for high-risk sensitized patients - the “Heidelberg Algorithm” - Morath, Christian; Opelz, Gerhard; Zeier, Martin; Süsal, Caner (Transplantation proceedings, 2011)
Presensitized patients on kidney transplant waiting lists have a lower chance of receiving a crossmatch-negative kidney and, if transplanted, are at increased risk of immunologic graft loss. We developed an algorithm for pretransplant risk estimation and peritransplant treatment which contains 7 independent steps: 1) pretransplant identification of high-risk patients; 2) good HLA match; 3) inclusion in the Acceptable Mismatch Program of Eurotransplant if applicable; 4 and 5) pre- and posttransplantation desensitization; 6) monitoring of donor-specific antibodies after transplantation; and 7) protocol biopsies. Between April 1, 2006, and March 31, 2009, 34 patients were transplanted according to this algorithm. Graft and patient survival rates did not differ from those in nonsensitized recipients. Antibody-mediated rejection episodes were <10% and infectious complications infrequent.
Gesehen am 07.09.2022